A Lawless Breed : John Wesley Hardin, Texas Reconstruction, and Violence in the Wild West - Parsons, Chuck (Book collections on Project MUSE., 2013)
John Wesley Hardin! His name spread terror in much of Texas in the years following the Civil War as the most wanted fugitive - a fugitive with a $4000 reward on his head. A Texas Ranger wrote that he killed men just to see them kick. Hardin began his killing career in the late 1860s and remained a wanted man until his capture in 1877 by Texas Rangers and Florida law officials. He certainly killed twenty men, though some credited him with killing forty or more. After sixteen years in Huntsville Prison, he was pardoned by Governor Hogg. For a short while, he avoided trouble and roamed westward, eventually establishing a home of sorts in wild and woolly El Paso as an attorney. He became embroiled in the dark side of that city and eventually lost his final gunfight to El Paso Constable John Selman. Hardin was forty-two years old. Besides his reputation as the deadliest man with a six-gun, he left an autobiography in which he detailed many of the troubles of his life. In this book, the authors have meticulously examined his claims against available records to determine how much of his life story is true, and how much was only a half truth or complete lie.